Reimagining Community Mental Health Care Services: Case Study of a Need Based Biopsychosocial Response Initiated During Pandemic - Sunder, Poornima; Vincent, Anu Sonia; Saju, Meenu K.; Moorthy, Anu S.; Paulose, Godson; Robins, Roshni; Prabhu, Anupama V.; Arun, M.; Rajah, Anita; Venkateswaran, Chitra (Frontiers in Psychiatry, 2021)
Community mental health systems worldwide have undergone unprecedented transformation in order to accommodate enormous demands of the pandemic and its mitigation efforts. The pandemic created unprecedented challenges that required Mehac Foundation (further referred as Mehac), a not for profit organization based in Kerala, to reassess our care delivery model. The aim of this study is to present a flexible, need-based psychosocial response effectuated by the NGO (Non Governmental Organization) with a focus on minimizing the impact of COVID 19 on vulnerable communities, while adhering to timely regulations issued by the government. The key aspect of our psychosocial response was implementation of a phased approach that was rooted in real time need identification. The strategies will be described under broad headings of (i) adaptations for maintaining continuity of care (ii) identifying vulnerable subgroups and need based psychological response (iii) exploring social dimensions of the pandemic and implementing strategies to address them (iv) ensuring team wellbeing and incorporating skill building to effectively respond to the challenges.